Extracellular vesicles meet mitochondria: Potential roles in regenerative medicine - Shujie Wu; Tao Yang; Meirui Ma; Le Fan; Lin Ren; Gen Liu; Yiqiao Wang; Bin Cheng; Juan Xia; Zhichao Hao (Elsevier, 2024)
Extracellular vesicles (EVs), secreted by most cells, act as natural cell-derived carriers for delivering proteins, nucleic acids, and organelles between cells. Mitochondria are highly dynamic organelles responsible for energy production and cellular physiological processes. Recent evidence has highlighted the pivotal role of EVs in intercellular mitochondrial content transfer, including mitochondrial DNA (mtDNA), proteins, and intact mitochondria. Intriguingly, mitochondria are crucial mediators of EVs release, suggesting an interplay between EVs and mitochondria and their potential implications in physiology and pathology. However, in this expanding field, much remains unknown regarding the function and mechanism of crosstalk between EVs and mitochondria and the transport of mitochondrial EVs. Herein, we shed light on the physiological and pathological functions of EVs and mitochondria, potential mechanisms underlying their interactions, delivery of mitochondria-rich EVs, and their clinical applications in regenerative medicine.